Overexpression of AmpC Promotes Bacteriophage Lysis of Ampicillin-Resistant Escherichia coli - Wang, Shuang; Yin, Bo; Yu, Ling; Dang, Mei; Guo, Zhimin; Yan, Guangmou; Hu, Dongliang; Gu, Jingmin; Du, Chongtao; Feng, Xin; Han, Wenyu; Adam, Yuren Yuan; et al. (Frontiers in Microbiology, 2020)
Infections caused by antibiotic-resistant Escherichia coli (E. coli) are a threat to human and animal health globally. Phage therapy has made a great progress in the treatment of drug-resistant infections, but it is still unclear whether E. coli resistance against antibiotics could change the lysis ability of phages. We demonstrate that AmpC, an important β-lactamase for ampicillin resistance, promotes bacteriophage lysing host E. coli. E. coli having higher expression of AmpC also showed higher level of OmpA production, which is localized on outer membrane of E. coli and served as a receptor for T-even phages, resulting in an increased phage adsorption rate and essentially increased sensitivity of E. coli to phage. These data demonstrate that increased ampicillin resistance can increase the sensitivity of E. coli to lytic phage to some extent, which provides evidence for the feasibility of synergistic application of phage and antibiotics.